Diagnostic-Therapeutic Pathway and Outcomes of Early Stage NSCLC: a Focus on EGFR Testing in the Real-World - Pasello, Giulia; Lorenzi, Martina; Pretelli, Giulia; Comacchio, Giovanni Maria; Pezzuto, Federica; Schiavon, Marco; Buja, Alessandra; Frega, Stefano; Bonanno, Laura; Guarneri, Valentina; Calabrese, Fiorella; Rea, Federico (Frontiers in Oncology, 2022)
Background: Osimertinib is considered the standard-of-care for previously-untreated EGFR mutant advanced non-small cell lung cancer (NSCLC). Oncogene driver screening in early NSCLC is not standard practice. A real-world study has been designed in order to investigate the optimal testing frequency and timing for EGFR mutations in early NSCLC in clinical practice. Patients and methods: The present observational, retrospective study evaluated the real-world diagnostic-therapeutic pathway and clinical outcomes of 225 patients with stage I-III NSCLC, with particular reference to the EGFR-mutant subgroup. Results: Prior to surgery, 101 patients had undergone a diagnostic biopsy; EGFR mutational analysis was available in 56 (55%) patients and 12 patients (21%) had a cancer harboring an EGFR mutation. Among surgical specimens, reflex EGFR test was performed in 181 (80%) of 225 and 35 cases (19%) were EGFR mutant. The majority of patients had not received adjuvant chemotherapy (N=174, 77%) or adjuvant radiotherapy (N=201, 89%). Of 49 (22%) patients experiencing disease relapse, 26 (53%) received first-line systemic treatment. All EGFR-mutant relapsed patients (N=6, 12.2%) received an EGFR-TKI. Median overall survival (OS) and relapse-free survival for the entire population were not reached. Multivariate analysis for OS confirmed a significant correlation with age, female gender, EGFR status, necrosis score, perineural invasion, and relapsed disease. EGFR test costs represented 1.6-2.4% of the total costs of management per patient (€34,340). Conclusions: Our results suggest that the frequency of EGFR mutations in early stage (I-III) NSCLC is similar to that of advanced stages. Reflex EGFR testing in all early-stage NSCLC at diagnosis or after surgery appears to be a valid tool to give patients the chance to benefit from targeted adjuvant treatment.